MY SAY: Of Peking duck and the burqa - Abd Razak, Dzulkifli (2008)
There will be one favourite delicacy less in Britain soon — the Peking duck! This follows a recent announcement that the dish will be banned throughout the UK. The action was reportedly taken as a result of a European Union (EU) ban on the ovens — a 6fthigh drumshaped device — traditionally used to prepare it. Said to be larger than a conventional commercial oven, it can roast up to 24 ducks at a time. It is heated by a central burner placed at the base which forced the air up between the skin and the meat, roasting them in the process. Hardest hit was Chinatown where apparently many ovens were sealed because they did not carry a CE (Comformite Europeenne, or European Compliance) mark; therefore, they did not meet the stipulated safety standards on carbonmonoxide emissions as laid down by Brussels.